EFEKTIVITAS PERATURAN MENTERI KELAUTAN DAN PERIKANAN REPUBLIK INDONESIA NOMOR 2 TAHUN 2015 TENTANG LARANGAN PENGGUNAAN ALAT PENANGKAPAN IKAN PUKAT HELA (TRAWL) DAN PUKAT TARIK (SEINE NETS) - Devi Lusiani (PROGRESIF: Jurnal Hukum, 2016)
The Regulation of the Ministry of Marine Affairs and Fisheries of the Republic of Indonesia Number2 of 2015 on the prohibition of the usage of trawl and seine nets to catch fish. The regulation includes the definition and standard for fishing gear and its types, and it is the implementing rules of Law Number 45 of 2009 on fishery. The purpose of this study is to examine the efficacy of the Regulation of the Ministry of Marine Affairs and Fisheries of the Republic of Indonesia Number 2 of 2015 on the Prohibition of using trawl and seine nets to catch fish. This study also aims to discover the strengths and weaknesses of the regulation. This is a juridicial empiricial research with juridicial empiricial approach. Based on the research, it is found that the regulation is deemed effective by the society, especially for fishermen. The regulation is effective in mitigating the damage of marine resources on the seabed. However, there is also a negative impact on the society.